Acute electrical, autonomic and structural effects of binge drinking: Insights into the 'holiday heart syndrome'. (15th May 2021) - Voskoboinik, Aleksandr; McDonald, Conor; Chieng, David; O'Brien, Jessica; Gutman, Sarah; Ngu, Phillip; Sugumar, Hariharan; Wong, Geoffrey; Kalman, Jonathan M.; Taylor, Andrew J.; Kistler, Peter M.
Abstract: Background: Binge drinking is a common atrial fibrillation (AF) trigger, however the mechanisms are poorly understood. Objective: To investigate the effects of alcohol intoxication and hangover with rhythm monitoring and cardiac MRI. Methods: Patients underwent serial cardiac MRI pre- and post-binge with continuous Holter monitoring. Time periods analyzed: baseline (24 h pre-binge), consumption, hangover (0– 24 h post-consumption) and post-hangover (24–48 h post-consumption). Results: 50 patients (age 49 ± 15 years, 40% paroxysmal AF) completed the study (intake 8.4 ± 3.1 standard drinks). Mean heart rate increased from 72 ± 10 to 80 ± 13 beats per minute (bpm) during consumption ( p  < 0.001). The hangover period was characterised by higher daily atrial ectopic count (50, IQR 10–132 vs baseline 43, IQR 10–113; p  = 0.04) and reduced heart rate variability (SDNN 55 ms, IQR 40–65 versus 62 ms, IQR 51–66; p  = 0.007). There was evidence of heightened parasympathetic activity post-hangover with heart rate slowing (mean HR 54 ± 6 bpm; p  = 0.03) and increased activity in the High frequency band when separating the complex heart rate variability waveform into its component rhythms (291 ms 2, 97–538 versus baseline 237 ms 2, IQR 104–332; p  = 0.04). Three patients developed AF 11, 29 and 34 h post-binge. Cardiac MRI (2.7 ± 0.7 days post-binge) demonstrated a decrease in left atrial (LA) emptying fraction (57.9 ± 8.5 to 53.5 ± 6.7%; p  = 0.003) but no change in LA volume, left ventricular ejection fraction or markers of ventricular inflammation. Conclusion: Binge drinking is associated with sympathetic activation followed by a 'rebound' parasympathetic response and atrial mechanical dysfunction which may explain the propensity and temporal association between binge drinking and AF. Highlights: Binge drinking appears to be is associated with sympathetic activation followed by a 'rebound' parasympathetic response. Subclinical mechanical atrial dysfunction was seen at 3 days post binge. No myocardial inflammation or change in ventricular function were seen up at 3 days post binge. Alcohol appears to have a relatively modest effect on burden of atrial ectopy.